Biomolecule incorporated poly-ε-caprolactone nanofibrous scaffolds for enhanced human meniscal cell attachment and proliferation1. Issue 90 (1st October 2015) - Gopinathan, J.; Mano, Steffie; Elakkiya, V.; Pillai, Mamatha M.; Sahanand, K. Santosh; Rai, B. K. Dinakar; Selvakumar, R.; Bhattacharyya, Amitava
<x xml:space="preserve">Abstract</x> Biomolecule incorporated PCL nanofibrous scaffolds supporting meniscal cell attachment and proliferation.